PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2012 DAN 2013 - Saputra, Yuda Dwi; Desmintari, Desmintari (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This objective of this research is to test the effect of Profitability,Liquidity and StructureAssets on Capital Structure. The independent variable in this study was Profitability,Liquidity and Structure Assets, while the dependent variable in this study is the CapitalStructure. The population of this research is 139 manufacturing companies listed on theIndonesia Stock Exchange 2012 and 2013 period. The data were obtained from publishedfinancial statements of the company. Through purposive sampling technique obtained atotal sample of 50 companies. The analysis technique used is multiple linear regressionusing IBM SPSS (Statistical Product and Service Solutions) version 21.0. The resultsshowed simultaneous Profitability, Liquidity and Structure Assets significant effect on theCapital Structure. While partially variables that doesn’t significantly influence theprofitability and Structure Assets of Capital Structure, while variable Liquiditysignificantly influence the Capital Structure.